Successful treatment of ulceration in hidradenitis suppurativa with topical bucladesine: A case report - Ichiro Kurokawa; Kanako Kita; Takashi Hashimoto (Wiley, 2024)
Abstract We report a case of hidradenitis suppurativa (HS) with skin ulceration in a 19‐year‐old man. He was successfully treated with topical bucladesine ointment treatment, resulting in a hypertrophic scar 2 months after the treatment. Bucladesine can be an alternative treatment option for ulceration in HS.